Four Level Simulation of MOSFET - M. N. Doja; Moinuddin; Umesh Kumar (Active and Passive Electronic Components)
In this paper a software (MOSOFT) has been developed for 4-level simulation of MOSFETS. This software simulates the device characteristics up to micron channel length and includes long channel, short channel, subthreshold and field dependent mobility degradation models.